KIT D816V and JAK2 V617F mutations are seen recurrently in hypereosinophilia of unknown significance - Schwaab, Juliana; Metzgeroth, Georgia; Naumann, Nicole; Jawhar, Mohamad; Gaiser, Timo; Hofmann, Wolf-Karsten; Fabarius, Alice; Reiter, Andreas (American journal of hematology, 2015)
Myeloproliferative neoplasms with eosinophilia are commonly characterized by a normal karyotype and remain poorly defined at the molecular level. We therefore investigated 426 samples from patients with hypereosinophilia of unknown significance initially referred for screening of the FIP1L1-PDGFRA (FP) fusion gene also for KIT D816V and JAK2 V617F mutations. Overall, 86 (20%) patients tested positive: FP+ in 55 (12%), KIT D816V+ in 14 (3%), and JAK2 V617F+ in 17 (4%) patients, respectively. To gain better insight into clinical characteristics, we compared these cases with 31 additional and well-characterized KIT D816V+ eosinophilia-associated systemic mastocytosis (SM-eo) patients enrolled within the “German Registry on Disorders of Eosinophils and Mast cells.” Significant differences included younger age, male predominance, and higher eosinophil counts for FP+ cases while abdominal lymphadenopathy, ascites, and serum tryptase levels >100 μg/l were characteristic for those with KIT D816V. Leukocytes, hemoglobin, and splenomegaly did not differ significantly. A median of three additional mutations, most frequently TET2 and SRSF2, were identified in 12/13 KIT D816V+ SM-eo patients with available material indicating a more complex molecular pathogenesis. Median survival was not reached for FP+ cases but was only 26 and 41 months for KIT D816V+ SM and JAK2 V617F+ MPN-eo, respectively. Eosinophilia of ≥2 × 109/l was identified as discriminator for inferior survival in KIT D816V+ and/or JAK2 V617F+ patients (median survival 20 months vs. not reached, P = 0.002). Thus, there is a clear prognostic and therapeutic rationale for detection of KIT D816V and JAK2 V617F in the diagnostic work up of eosinophilia.
Gesehen am 08.03.2018